2012
DOI: 10.1080/1331677x.2012.11517510
|View full text |Cite
|
Sign up to set email alerts
|

Business Tourism Destination Competitiveness: A Case of Vojvodina Province (Serbia)

Abstract: T he main purpose of this article is to create model of business tourism destination competitiveness and test it on the example of Vojvodina Province, tourist cluster in Serbia, where business tourism is defined as one of key tourist products. The paper aims to examine in which areas Vojvodina Province is more competitive as a business tourism destination and where it is less competitive compared to "competitive set" of three chosen destinations. Also, this paper aims to test relationships between destination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 44 publications
2
29
0
7
Order By: Relevance
“…The constructs for the questionnaire are adapted from previous literature and then tailored to the context of this study. Following Dragićević et al (2012), this study defines green tourism marketing as promotional activities of tourism products/services in a way that does not result in any negative impact on the environment. The concept of green tourism is measured based on four aspects: core resources, attractor, supporting factor and amplifying determinant.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The constructs for the questionnaire are adapted from previous literature and then tailored to the context of this study. Following Dragićević et al (2012), this study defines green tourism marketing as promotional activities of tourism products/services in a way that does not result in any negative impact on the environment. The concept of green tourism is measured based on four aspects: core resources, attractor, supporting factor and amplifying determinant.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, green marketing can be used as a tool for sustainable growth. Dragićević, Jovičić, Blešić, Stankov and Bošković (2012) suggested that the concept of green tourism marketing entails:…”
Section: Green Tourism Marketingmentioning
confidence: 99%
“…Damanik (2013) menyatakan bahwa dalam mendefinisikan daya saing dapat dilihat melalui dua sudut pandang yaitu sudut pandang makro atau sudut pandang manajemen, dalam sudut pandang makro ditentukan oleh faktor sumber daya (alam dan manusia), struktur organisasi, suasana persaingan, dan strategi yang digunakan, sedangkan dalam sudut pandang manajemen daya saing berhubungan dengan pengalokasian sumber daya yang dimiliki untuk mencapai tujuan. Dragicevic et al, (2012) menyatakan bahwa dalam menilai daya saing dapat dilihat melalui dua dimensi besar yaitu keunggulan komparatif dan keunggulan kompetitif. Keunggulan komparatif dapat didefinisikan sebagai segala sesuatu yang melekat pada destinasi wisata, baik yang secara alami ada atau dibuat untuk tujuan tertentu yang berkaitan dengan pariwisata, sedangkan keunggulan bersaing didefinisikan sebagai kemampuan destinasi wisata untuk memanfaatkan sumber daya yang dimiliki seefisien dan seefektif mungkin pada jangka waktu yang lama (Estevão et al, 2016).…”
Section: Kajian Teoriunclassified
“…Domestic markets are vital since they generate income, create jobs and extend the off-season utilization of capital resources (Archer, 1978). Therefore, there is a substantial motive for governments, institutions, stakeholders, investors, marketers and local communities to invest and develop the domestic tourism markets (Armenski, Gomezelj, Djurdjev, Đeri, & Dragin, 2011;Dragićević, Jovičić, Blešić, Stankov, & Bošković, 2012;Dwyer et al, 2014;Popesku & Pavlovic, 2013;Teodorović & Popesku, 2017). Domestic tourism markets are different from foreign ones.…”
Section: Introductionmentioning
confidence: 99%